UTILIZATION OF ACTIVATED CARBON FROM ELEPHANT GRASS (PENNISETUM PURPEREUM) AND MANGANESE DIOXIDE AS SUPERCAPACITOR ELECTRODES - Fathi Marzuqi; Erna Frida; Syahrul Humaidi (RADJA PUBLIKA, 2025)
The growing need for sustainable and eco-friendly energy storage solutions has led to advancements in high-performance supercapacitors with extended cycle life. This research explores the fabrication of composite electrodes using activated carbon derived from elephant grass (Pennisetum purpureum) combined with manganese dioxide (MnO₂). The carbon material was produced through chemical activation with potassium hydroxide (KOH) and subsequent physical activation using carbon dioxide (CO₂). MnO₂ was incorporated into the activated carbon at various weight ratios (10:0, 7:3, 5:5, 3:7, and 0:10). Morphological and elemental analyses were performed using SEM-EDS, Meanwhile, the electrochemical performance was evaluated using galvanostatic charge-discharge (GCD) tests and electrochemical impedance spectroscopy (EIS). Of all the samples evaluated, the composite containing a 3:7 ratio of carbon to MnO₂ exhibited the highest specific capacitance, reaching 198.51 F/g, highlighting the beneficial interaction between double-layer capacitance and pseudocapacitance. These findings suggest that elephant grass-derived carbon, when effectively combined with MnO₂, presents a cost-effective and environmentally friendly option for next-generation supercapacitor electrodes.